Market Discipline and Bank Risk Taking: Evidence from the East Asian Banking Sector - Hamid, Fazelina Sahul; Yunus, Norhanishah Mohd (Korea Institute for International Economic Policy (KIEP), 2017)
The third pillar of the Basel II highlights the role of market discipline in easing the existing pressure on traditional monitoring measures like capital requirement and government supervision. This study test the effectiveness of market discipline in inducing prudential risk management practices among the East Asian banks over the 1995 to 2005 period. Market discipline is measured using information disclosure and interbank deposit holdings. We find that only the latter is an effective market discipline tool. However, the former becomes effective when market concentration is higher. We find that government owned, foreign owned and recapilatised banks are subject to market disciplining when disclosure in taken account but the opposite is true when interbank deposits is taken into account. Finally, we find that banks that disclose more risk related information hold more capital against their non-performing loan. The implications of the findings are discussed.